Views on Islamic Criminal Law and Law No. 22 of 2009 about LLAJ against Traffic Violations on the Sendal Jepit Road, Pematang Siantar City - Siregar, Azril Arifin; Syahmedi Siregar, Ramadhan (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
The notion of jarimah or criminal offense, a criminal act is an act or behavior that is prohibited by Sharia which is punishable by had and tazir penalties. Without realizing that violating traffic is a crime, people who go against the flow of traffic can be subject to sanctions in accordance with Article 287 Paragraph 1 of Law No. 22 of 2009 concerning road traffic and transportation. Traffic flow regulations for motorists, either motorbikes or cars, are not explained directly in Islamic jurisprudence, but in general, Islam always stays away from things that can bring harm to the surrounding community. The formulation of the problem in this journal is how Islamic criminal law and Law No. 22 of 2009 concerning LLAJ deal with violations that have occurred. The purpose of this study is to find out the views of Islamic criminal law and Law No. 22 of 2009 concerning LLAJ regarding violations that have occurred. The method used is a qualitative normative-empirical approach and the nature of the research is descriptive. Primary data sources are in the form of interviews, observations, and questionnaires. The interviews that the researchers used were in the form of unstructured interviews and distributed questionnaires to OJOL (motorcycle taxis online) and road users. Traffic violations can lead to accidents, which are certainly very detrimental to oneself or many people. In a year the highest accident rate that the authors get is 12 times a year with the vehicle used in the form of a motorbike. The factors that influence violations on the Sendal Jepit Road in the city of Pematang Siantar, namely: speeding up travel routes, avoiding police, and the habit of going against the direction.